2018
DOI: 10.1080/23288604.2018.1440344
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Initiatives that Link Provider Payment with Quality Measurement of Maternal Health Services in Low- and Middle-Income Countries

Abstract: Abstract-To reduce maternal and newborn morbidity and mortality, health care payers are experimenting with ways to better align incentives to promote high-quality maternal health services. This review examined 26 recent initiatives of health care payers in 16 low-and middle-income countries to pay for quality, and not solely quantity, of maternal health services. Payers measured quality by assessing availability of structural inputs (24 of 26 cases), adherence to processes (25 of 26 cases), and observation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Even as few studies explicitly link country context to PBF implementation and its impact on quality of care, these results are in line with other evaluations: across a wide range of countries, PBF’s impact on quality was found to benefit structural dimensions of quality more than process and outcome measures. 18 A recent study from Mali using a very similar approach 19 also identified the significant role of baseline implementation context, specifically in terms of the role and capacity of decentralised entities prior to implementation. Studies from Benin, Democratic Republic of the Congo, Rwanda and Zambia demonstrate that the conditionality aspect of PBF is associated with improved reporting and improved provider motivation, improved provider effort for incentivised services, with limited to no positive impact for non-incentivised services.…”
Section: Discussionmentioning
confidence: 99%
“…Even as few studies explicitly link country context to PBF implementation and its impact on quality of care, these results are in line with other evaluations: across a wide range of countries, PBF’s impact on quality was found to benefit structural dimensions of quality more than process and outcome measures. 18 A recent study from Mali using a very similar approach 19 also identified the significant role of baseline implementation context, specifically in terms of the role and capacity of decentralised entities prior to implementation. Studies from Benin, Democratic Republic of the Congo, Rwanda and Zambia demonstrate that the conditionality aspect of PBF is associated with improved reporting and improved provider motivation, improved provider effort for incentivised services, with limited to no positive impact for non-incentivised services.…”
Section: Discussionmentioning
confidence: 99%
“…Following the literature (10,12,32), we posit that capitation will affect CS rates through a number of channels. We expect capitation to improve gatekeeping, adherence to guidelines and continuity of care ensured by the preferred primary provider (PPP) requirement.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Accountability mechanisms have typically accompanied these to counter each payment system's deleterious effects, especially the provision of sub-optimal or unnecessary care. The evidence of these payment mechanisms on maternal healthcare has been mixed, both in high income countries (12) and in LMICS (13).…”
Section: Introductionmentioning
confidence: 99%
“…Health systems have developed different payment systems to balance incentives for service provision with the need for cost control [2]. However, many of these payment system reforms have mixed results on service provision [2,3] and maternal health services in particular [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Capitation as a payment mechanism is uncommon in African health systems. Currently, many African countries are using capitation in combination with other payment methods [24,25]. Kenya is a case in point where capitation was combined with Fee for Service for provider payment [24].…”
Section: Introductionmentioning
confidence: 99%